Echos of readings: from the forgotten Adherbal de Carvalho, The Bride - Wimmer, Norma [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2021)
Naturalism, as it was practiced in France, aroused the interest of a great number of followers in Brazil. This fact seems to have occurred because, on the one hand, the romantic spirit, associated in Brazil to the monarchic regime itself, seemed to have its sources of inspiration exhausted; on the other hand, the modern scientific spirit, associated to the republican thought, was gradually pushing the artistic production in general, and particularly the literary one, in another direction: the rigorous observation of facts, the presentation of the truth was essential. Among the Brazilian authors who tried to follow the new trend disseminated by Zola and his experimental novel, many were relegated to oblivion. This is the case, for example, of Adherbal de Carvalho who, besides critical studies, poetry and translations published, in 1888, in Sao Paulo, The Bride (A Noiva) - sketch of a naturalistic novel - his only prose fiction. Very little is said, nowadays, about this novel and only rare copies of it still survive. The purpose of the work presented here is to recover Carvalho's text and to locate in it echoes of naturalism as practiced by Zola, as well as to recover reading memories of the works of other authors such as Flaubert and Dumas.
Keywords: Adherbal de Carvalho; The Bride; Brazilian Naturalism